2022
DOI: 10.1002/chir.23456
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐scale synthesis of (S)‐1‐(thiophen‐2‐yl)ethanol in high enantiomeric purity under Enterococcus faecium BY48 biocatalysts

Abstract: Sulfur‐containing chiral heterocyclic secondary alcohols are relevant intermediates in the preparation of enantiomerically pure compounds endowed with biological activity. In this report, we evaluated the reductive potential of different lactic acid bacteria as whole‐cell biocatalysts of the enantioselective reduction of 1‐(thiophen‐2‐yl)ethanone (1). Enterococcus faecium BY48, isolated from boza, a cereal‐based fermented beverage, was found to be the best biocatalyst in our initial investigations. Using whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Engin Sahin further reported the bioreduction of 1-(thiophen-2-yl)ethanone to ( S )-1-(thiophen-2-yl)ethanol using the lactic acid bacterium Enterococcus faecium BY48. 50 This method offered an alternative green approach to the chemical synthesis of sulfur-containing chiral heterocyclic secondary alcohols. The same research group reported the bioreduction of a variety of prochiral ketones to their respective ( R )-alcohols using whole cells of Lactobacillus kefiri P2.…”
Section: Whole-cell Redox Biocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Engin Sahin further reported the bioreduction of 1-(thiophen-2-yl)ethanone to ( S )-1-(thiophen-2-yl)ethanol using the lactic acid bacterium Enterococcus faecium BY48. 50 This method offered an alternative green approach to the chemical synthesis of sulfur-containing chiral heterocyclic secondary alcohols. The same research group reported the bioreduction of a variety of prochiral ketones to their respective ( R )-alcohols using whole cells of Lactobacillus kefiri P2.…”
Section: Whole-cell Redox Biocatalysismentioning
confidence: 99%
“…The final mutant, I91V/I187S/I188L/Q191N/F205A (F12), showed 183-fold enhanced specific activity. A preparative scale reduction of 49 at a substrate concentration of 20 g L −1 by wet cells coexpressing RasADH F12 and GDH produced (13R,17S)-ethyl secol (50) with 99% conversion in 6 h, with >99.5% stereoselectivity and a yield of 94%.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%